2016
DOI: 10.1016/j.celrep.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Nat1 Deficiency Is Associated with Mitochondrial Dysfunction and Exercise Intolerance in Mice

Abstract: Summary We recently identified human N-acetyltransferase 2 (NAT2) as an insulin resistance (IR) gene. Here we examine the cellular mechanism linking NAT2 to IR and find that Nat1 (mouse ortholog of NAT2) is co-regulated with key regulators of mitochondria. RNA-interference mediated silencing of Nat1 led to mitochondrial dysfunction characterized by increased intracellular reactive oxygen species and mitochondrial fragmentation as well as decreased mitochondrial membrane potential, biogenesis, mass, cellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 54 publications
7
43
0
Order By: Relevance
“…We also show that absence of the two Nat genes leads to an increase in the concentration of hepatic CoA in mice on a HFHS diet. Since CoA is overwhelmingly concentrated in the mitochondria, our study reinforces previous observations concerning mitochondrial anomalies in Nat1 KO cancer cells [33] or in Nat1 KO mice [4,5] and opens the way to studies on possible mitochondrial dysfunctions in cases of NAT enzyme deficiency (as in human NAT1/2 slow acetylators). However, the aforementioned in vivo studies [4,5] demonstrated that reduced mitochondrial activity was associated with a systemic insulin resistance in Nat1 KO mice.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We also show that absence of the two Nat genes leads to an increase in the concentration of hepatic CoA in mice on a HFHS diet. Since CoA is overwhelmingly concentrated in the mitochondria, our study reinforces previous observations concerning mitochondrial anomalies in Nat1 KO cancer cells [33] or in Nat1 KO mice [4,5] and opens the way to studies on possible mitochondrial dysfunctions in cases of NAT enzyme deficiency (as in human NAT1/2 slow acetylators). However, the aforementioned in vivo studies [4,5] demonstrated that reduced mitochondrial activity was associated with a systemic insulin resistance in Nat1 KO mice.…”
Section: Resultssupporting
confidence: 88%
“…Interestingly it has been shown, using Nat2 KO mice, that mouse NAT2/human NAT1 play a role in folate metabolism through acetylation of folate metabolite para‐aminobenzoylglutamate . Phenotype differences observed between our study and the above mentioned studies may also rise from environmental differences in particular in animal diets.…”
Section: Resultsmentioning
confidence: 43%
“…The changes in mitochondrial function in the MDA-MB-231 and HT-29 cells are similar to those reported in murine cells following Nat1 knockout (Camporez et al, 2017;Chennamsetty et al, 2016). Nat1 is the murine homolog of human NAT2, not NAT1, so the similarity in responses following gene deletion was unexpected.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, single nucleotide polymorphisms in the NAT2 gene, which result in a slow acetylator phenotype, were shown to be associated with insulin resistance (Knowles et al, 2015). Moreover, deletion of the murine homolog of human NAT2 (Nat1) recapitulated the insulin resistance phenotype (Camporez et al, 2017), increased mitochondrial dysfunction and the production of reactive oxygen species (ROS) (Chennamsetty et al, 2016). Nat1 knockdown in 3T3-L1 cells with sh-RNA decreased both basal respiration as well as reserve respiratory capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, a recent European GWAS reported that a nonsynonymous variant of N-acetyltransferase 2 (NAT2) is associated with insulin resistance and related traits as well as with decreased adipocyte differentiation, insulin-mediated glucose uptake and increased WAT lipolysis 95 . Silencing or knocking down the mouse NAT2 orthologue, NAT1, induces insulin resistance, glucose intolerance and exercise intolerance 96,97 , and is associated with ectopic accumulation of TAG and DAG accumulation and activation of hepatic PKCε and muscle PKCθ 97 . Nat1 −/− mice also display mild reductions in mitochondrial function and altered morphology, demonstrating another genetic link between reduced mitochondrial function, TAG and DAG deposition and nPKC-induced liver and muscle insulin resistance 97 .…”
Section: Insulin Resistance In Skeletal Musclementioning
confidence: 99%